The impact of gut microbiota on the pathogenesis of type 1 diabetes in children: Current evidence and potential interventions - Muda, Martyna; Bachurski, Patryk; Chmiel, Gabriela; Kalinowski, Paweł; Międlar, Maja; Pacek, Szymon; Pierzga, Elisabetta; Wiśniewski, Karol Paweł; Witkowski, Paweł; Zarański, Bartosz (Quality in Sport, 2026)
Type 1 diabetes (T1D) is a chronic autoimmune disease characterized by selective destruction of pancreatic β‑cells, resulting in an absolute insulin deficiency and the need for lifelong replacement therapy from the time of diagnosis. At the same time, the role of the gut microbiota has been increasingly emphasized; under conditions of eubiosis, it participates in digestion, production of key metabolites, maturation of the immune system, and maintenance of intestinal barrier integrity. The aim of this paper is to present the role of the gut microbiota–immune system axis in the pathogenesis of T1D in children. We discuss evidence showing that children with T1D exhibit a characteristic dysbiosis: reduced microbial diversity, decreased abundance of short‑chain fatty acid (SCFA)‑producing bacteria, and a predominance of Gram‑negative bacteria. The consequences include weakening of the intestinal barrier (“leaky gut”), chronic low‑grade inflammation, and enhancement of autoimmunity against β‑cells. We present findings from cross‑sectional and prospective studies, as well as animal models, indicating that alterations in the microbiota and increased intestinal permeability may precede the clinical manifestation of T1D. Potential microbiota‑targeted interventions are also outlined, including dietary strategies, prebiotics, probiotics, and modulation of SCFA.